A starch gel material based on 4D printing technology and its preparation method and application

The oxidized starch gel was prepared through 4D printing technology, which solved the problem of insufficient stability of polysaccharide iron complex in the gastrointestinal tract, achieved efficient release and absorption of iron ions, restored the anemic state of iron-deficient mice, and reduced preparation costs.

CN118878914BActive Publication Date: 2025-09-26SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410963061.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-09-26
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

Existing polysaccharide iron complexes as iron supplements have problems such as scarce raw materials, high prices, complex separation and purification, and insufficient stability in the gastrointestinal tract. Traditional powder dosage forms are unstable in release in the gastrointestinal tract, making it difficult to achieve efficient absorption.

Method used

Oxidized starch gel is prepared using 4D printing technology. By introducing carboxyl groups into starch molecules and combining them with metal ions, a three-dimensional gel network structure is constructed using hot extrusion. This controls its stability in the stomach and rapidly releases iron ions in the proximal small intestine, achieving efficient absorption.

Benefits of technology

It achieves efficient release and absorption of iron ions, reduces preparation costs, and restores the anemic state of iron-deficient mice. It has good iron supplementation effect and industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004950879710000111
    Figure BDA0004950879710000111
  • Figure BDA0004950879710000112
    Figure BDA0004950879710000112
  • Figure BDA0004950879710000121
    Figure BDA0004950879710000121
Patent Text Reader

Abstract

The present invention belongs to the technical field of starch hydrogel materials, and discloses a starch gel material based on 4D printing technology and its preparation method and application, the preparation method comprising the following steps: (1) gelatinizing a mixture of carboxyl starch and water, and adding an iron source to obtain a uniform mixture; (2) transferring the mixture to the barrel of a 3D printer, and printing and shaping through hot extrusion 3D, obtaining a 3D printed sample and performing 4D printing stimulation; the 4D printing stimulation is an alkali liquor stimulation, and the pH of the alkali liquor is 8-12; (3) the 4D printed sample is immediately frozen, and then vacuum freeze-dried to obtain a starch gel material. The present invention applies hot extrusion 4D printing technology to the preparation of a starch-based mineral supplement for the first time, which can suppress the release of iron ions in the stomach and achieve efficient iron supplementation. The present invention has simple process, is environmentally friendly, and is easy to repeat and mass-produce.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of 4D printing technology, and in particular relates to a starch gel based on 4D printing technology, and a preparation method and application thereof. Background Art

[0002] Iron Deficiency Anemia (IDA) is a common disease that seriously affects people all over the world. The latest research from the World Health Organization (WHO) shows that 2 billion people worldwide suffer from iron deficiency anemia to varying degrees. The root cause of iron deficiency anemia is the lack of iron in the body, which cannot meet normal physiological and metabolic needs, eventually leading to the obstruction of hemoglobin synthesis in red blood cells, and then causing anemia. In response to the challenges of iron deficiency anemia, the development of health care products for prevention and treatment is particularly urgent, especially for susceptible groups such as children, pregnant women and the elderly. In summary, research and development of supplements with excellent iron supplementation effects has become the most effective and practical strategy for the prevention and treatment of iron deficiency anemia, and it is currently the most pressing problem to be solved in the field of mineral nutrition supplementation.

[0003] Polysaccharide Iron Complex (PIC) is a novel iron supplement that is non-irritating to the gastrointestinal tract, exhibits significant iron-boosting effects, and exhibits high stability, making it a current focus of iron supplement research. Polysaccharides, as iron ligands, can form complexes with trivalent iron ions through the coordination and complexation of hydroxyl and carboxyl groups on the polysaccharide molecular chains. In the gastrointestinal tract, PIC is absorbed as a polysaccharide-iron molecule by the proximal small intestinal epithelial cells, resulting in high bioavailability and minimal gastrointestinal side effects associated with iron absorption. While PIC possesses these advantages, traditional pharmaceutical polysaccharides also have several disadvantages, including scarce raw materials, high cost, and complex isolation and purification requirements. In particular, traditional pharmaceutical polysaccharide-iron complexes require complex pretreatment to achieve water solubility and absorption in the proximal small intestine. These factors hinder the further development of PIC. Furthermore, traditional PICs are often formulated as powders, and their stability in the gastrointestinal tract is a key consideration.

[0004] Starch, as a natural polysaccharide polymer compound, occupies a dominant position in the human dietary energy source. Its low price and good biocompatibility make it highly favored in drug delivery. The multiple hydroxyl functional groups contained in starch molecules can increase the coordination sites for iron ions, and some of the hydroxyl groups of starch molecules can be oxidized to carboxyl groups through oxidation reactions, further improving its iron ion complexing ability and stability, thereby increasing its applicability as an iron supplement. In addition, starch, as a daily energy source for humans, can be digested and broken down into absorbable oligosaccharides and glucose by pancreatic amylase in the small intestine, which perfectly meets the absorption requirements of polysaccharide iron complexes. However, the research on starch-iron complexes is still in its preliminary stage, and the intrinsic relationship between its complexation mechanism and iron supplementation performance has not yet been elucidated.

[0005] The high swelling and water-holding capacity of starch hydrogels make them suitable for constructing three-dimensional network-structured controlled-release delivery systems. Compared to other delivery systems, they offer superior active substance release and biosafety. Active substances such as mineral iron ions can be released through degradation of the gel structure or diffusion along a concentration gradient. Modification of the starch molecular structure can also impart further stimuli-responsive properties. The complex stability of oxidized starch with iron ions is not only related to the functional groups of the starch molecules but also influenced by the network structure of the gel itself. Therefore, further manipulation of the strength and structure of oxidized starch gels through appropriate physical modification methods is crucial. Hot extrusion 4D printing, as a novel physical processing technology, allows printed gels to adapt their structure and functionality in response to external stimuli. Starch's rheological properties give it excellent printability, but during the printing process, hydrothermal and extrusion effects cause structural changes in the starch gel. Optimizing the gel properties and digestibility of 3D hydrogel structures generated by hot extrusion printing opens new avenues for personalized and precise customization of nutritional and health-promoting mineral foods and pharmaceuticals. However, to date, few studies have reported on the use of hot extrusion 4D printing to construct mineral-starch gel delivery systems. Summary of the Invention

[0006] To address the above issues, the present invention aims to provide a method for preparing starch gels based on 4D printing technology and its application. This method, which can be used for starches from various sources as well as physically or chemically modified starches, cleverly introduces carboxyl groups into starch molecules through oxidative modification to achieve binding with metal ions while simultaneously reducing starch molecular weight. Using hot extrusion 4D printing technology to construct oxidized starch gels and enhance the ionic complexation between the two, this method achieves efficient release and absorption of metal ions in the proximal small intestine, resulting in an ideal mineral supplementation effect.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing an iron-starch gel material based on 4D printing technology comprises the following steps:

[0009] (1) gelatinizing a mixture of carboxyl-containing starch and water, and adding a salt containing a divalent or higher metal cation to obtain a uniform mixture;

[0010] (2) transferring the mixed material into the barrel of a 3D printer, forming the mixed material by hot extrusion 3D printing, obtaining a 3D printed sample, and performing 4D printing stimulation; the 4D printing stimulation is alkaline solution stimulation, and the pH of the alkaline solution is 8-12;

[0011] (3) The 4D printed sample was immediately frozen and then freeze-dried in a vacuum to obtain an iron-starch gel material.

[0012] Preferably, the carboxyl-containing starch is one or more of oxidized starch and carboxymethyl starch; and the divalent or higher metal cations are one or more of ferric ions, ferrous ions, calcium ions and zinc ions.

[0013] Preferably, the starch is one or more of corn starch, tapioca starch, potato starch, chestnut starch and modified starches thereof.

[0014] Preferably, the method for preparing oxidized starch comprises the following steps: mixing starch with a buffer solution, then adding an oxidizing agent, stirring and reacting at a temperature of 0-40°C for 4-24 hours, and washing and drying after the reaction to obtain the oxidized starch. Preferably, the drying temperature is 35-55°C.

[0015] Preferably, the oxidant is sodium hypochlorite, TEMPO or laccase; the buffer is phosphate buffer; and the mass concentration of starch in the buffer is 0.01 to 0.5 g / mL.

[0016] Preferably, the starch concentration in step (1) is 10-50%, and the salt containing divalent or higher metal cations accounts for 1%-50% of the dry basis of starch; and the gelatinization conditions are gelatinization at 60-110° C. for 3-60 min.

[0017] Preferably, the conditions for the hot extrusion 3D printing molding are: a holding temperature of 55 to 100° C., a holding time of 5 to 30 minutes, and a cube, cuboid, or cylindrical model.

[0018] Preferably, the pH of the alkali solution stimulated by 4D printing is 8-10, the stimulation time is 0.1h-24h, the type of alkali solution is not limited, and preferably one or more of sodium hydroxide, potassium hydroxide, carbonate, bicarbonate, sulfite, acetate, silicate, phosphate, metaaluminate, hypochlorite and buffer solutions thereof.

[0019] The starch gel material prepared by the above method is used in the preparation of starch-based mineral supplements and delivery system materials, preferably as an iron supplement. In addition to iron, the minerals may also be calcium, zinc, etc.

[0020] Based on the influence of changing physiological environmental conditions in the human digestive tract on the interaction between metal ions (iron ions) and oxidized starch, this method uses specific 4D printing conditions, such as pH, to stimulate the molecular motion and interaction of the corresponding metal ions and oxidized starch. This rationally controls their coordination and complexation, resulting in a polysaccharide-metal complex with good formability, gastric stability, and subsequent rapid release in the proximal small intestine. This allows the construction of a 4D-printed oxidized starch gel with efficient mineral absorption.

[0021] Compared with the prior art, the present invention has the following outstanding advantages:

[0022] (1) The present invention applies hot extrusion 4D printing technology to the application of starch-based mineral supplements for the first time. Carboxyl groups are cleverly introduced into starch molecules through oxidative modification to achieve ionic bonding with divalent metal ions and simultaneously reduce the molecular weight of starch. Hot extrusion 4D printing technology is used to construct oxidized starch gel and strengthen the ionic complexation between the two, thereby inhibiting the release of iron ions in the stomach.

[0023] (2) The present invention constructs a three-dimensional gel network structure oxidized starch gel material based on the physical processing method of hot extrusion 4D printing technology. After starch reaches the small intestine, it can be further degraded into small molecules by amylase, thereby achieving rapid release and efficient absorption of metal elements in the proximal small intestine, so that starch can be used to prepare mineral supplements to replace the more expensive small molecule polysaccharide raw materials, thereby reducing costs.

[0024] (3) 4D printed iron-starch gel can effectively restore the anemic state of iron-deficient mice, and its biochemical indicators, blood routine indicators, and serum iron indicators can all be restored to normal levels. Overall, it can further regulate the body's iron metabolism and secretion by promoting the production of hepcidin in the liver of iron-deficiency anemic mice, thereby achieving efficient iron supplementation.

[0025] (4) The 4D printed starch gel prepared by the present invention has an excellent mineral supplementation effect, and the preparation method is simple, easy to repeat and mass-produce, and suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Product pictures of different embodiments.

[0027] Figure 2 The figures are scanning electron microscope images, EDS images and element distribution diagrams of different embodiments.

[0028] Figure 3The figures are scanning electron microscope images of different embodiments and control examples. DETAILED DESCRIPTION

[0029] The present invention will be described in further detail below with reference to examples and drawings, but the embodiments of the present invention are not limited thereto.

[0030] Example 1

[0031] Step 1: Mix starch and phosphate buffer to form a 40% suspension by mass, stir evenly at a speed of 200 r / min, adjust the pH value of the system to 8.0 with sodium hydroxide, then add NaClO solution (effective chlorine content 7.5% w / w based on starch dry basis) dropwise, and react at room temperature for 3 hours. During the addition process, monitor the change in pH in the reaction system, and ensure that the pH value of the reaction system is approximately 8.0-8.05 by adding sodium hydroxide solution dropwise. After 3 hours, neutralize with 10% dilute sulfuric acid, and wash the precipitate with deionized water until no precipitate is formed when AgNO3 solution is added to the supernatant, and then wash twice with anhydrous ethanol. Place in an oven to dry, and grind to pass through an 80-mesh sieve to obtain oxidized starch OMS with a carboxyl content of 1.0%.

[0032] Step 2: Oxidized starch and deionized water are mixed in a certain ratio (the dry weight of oxidized starch after mixing is 32%), and then 5% by mass of FeCl3·6H2O is added based on the dry weight of starch, and the pH is adjusted to 3.5 with hydrochloric acid. Then, it is placed in a 75°C water bath and stirred at a speed of 100 rpm / min for 45 minutes. The gelatinized sample is transferred to the printer barrel and kept at 25°C for 5 minutes. Before starting to print, the "Extrude" button is used to extrude the material into the nozzle. Finally, a small square model with a size of 20*20*5mm is selected for printing. The set nozzle parameters include: nozzle inner diameter of 0.8mm, nozzle relative height of 1.0mm, retraction speed of 50mm / s, retraction distance of 2mm, and printing speed of 30mm / s.

[0033] Step 3: The hot-extruded 3D printed iron-starch gel small cube models were soaked in NaOH solutions of different pH values ​​(pH 10), then placed in a -80°C refrigerator for 24 hours, and then placed in a vacuum freeze dryer for freeze drying to obtain the hot-extruded 4D printed iron-starch gel material 4D-FeOMS-5%.

[0034] Example 2

[0035] The difference between this embodiment and embodiment 1 is that in step 2, the amount of FeCl3·6H2O used is 10% of the dry weight of starch, and the hot extrusion 4D printing iron-starch gel material 4D-FeOMS-10% is prepared.

[0036] Example 3

[0037] The difference between this embodiment and embodiment 1 is that in step 2, the amount of FeCl3·6H2O used is 15% of the dry weight of starch, and the hot extrusion 4D printing iron-starch gel material 4D-FeOMS-15% is prepared.

[0038] Example 4

[0039] The difference between this embodiment and embodiment 2 is that in step 3, the stimulation pH is 8, and the hot extrusion 4D printing iron-starch gel material 4D-FeOMS10%-8 is prepared.

[0040] Example 5

[0041] The difference between this embodiment and embodiment 2 is that in step 3, the stimulation pH is 12, and the hot extrusion 4D printing iron-starch gel material 4D-FeOMS-10%-12 is prepared.

[0042] Example 6

[0043] The difference between this embodiment and embodiment 2 is that the amount of available chlorine used in step 1 is 10% of the dry weight of starch, and the oxidized starch hemostatic gel material 4D-10% FeOMS1 is prepared.

[0044] Example 7

[0045] The difference between this embodiment and embodiment 1 is that in step 2, FeCl3·6H2O is replaced by FeSO4 to prepare the hot extrusion 4D printing iron-starch gel material 4D-Fe2OMS-10%.

[0046] Example 8

[0047] The difference between this embodiment and embodiment 2 is that in step 1, the oxidized starch is prepared by the method and in step 2, the oxidized starch and deionized water are mixed in a certain ratio (the dry weight of the oxidized starch after mixing is 15%) to prepare the hot extruded 4D printing iron-starch gel material 4D-FeOMS2-10%.

[0048] Step 1: Accurately weigh 5 g of commercially available corn starch (dry basis) in 100 mL of 0.1 M phosphate-citrate buffer (pH 5). TEMPO (15% w / w based on the dry weight of the starch) and laccase (6% w / w based on the dry weight of the starch) were added at room temperature and stirred at room temperature for 12 hours at 200 rpm. After the reaction, the reaction product was filtered through a Buchner funnel and washed five times with 500 mL of deionized water until the laccase (food-grade laccase, sourced from Sigma-Aldrich, USA) and TEMPO were completely removed. The filter cake was then dried in an oven at 45°C, ground, and sieved for later use to produce C6-OMS, a C6-directed modified oxidized starch.

[0049] Example 9

[0050] The difference between this embodiment and embodiment 2 is that in step 1, corn starch is replaced with potato starch to prepare the hot extrusion 4D printing iron-starch gel material 4D-FeOPS-10%.

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 1 is that no iron element is added in the steps of this comparative example to obtain the comparative example sample 4D-OMS.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 1 is that this comparative example does not include the pH stimulation process in step 3, so that the sample 3D-5% FeOMS of Comparative Example 2 is obtained.

[0055] Comparative Example 3

[0056] The difference between this comparative example and Example 2 is that this comparative example does not have the pH stimulation process in step 3, that is, the sample 3D-10% FeOMS of Comparative Example 2 is obtained.

[0057] Comparative Example 4

[0058] The difference between this comparative example and Example 3 is that this comparative example does not have the pH stimulation process in step 3, that is, the sample 3D-15% FeOMS of Comparative Example 2 is obtained.

[0059] Comparative Example 5

[0060] The difference between this comparative example and Example 2 is that this comparative example directly uses corn starch to prepare comparative example 3 sample 4D-FeMS.

[0061] Comparative Example 6

[0062] The difference between this comparative example and Example 2 is that this comparative example directly uses the same amount of FeCl3 H2O without going through steps 1, 2, and 3, to obtain the comparative example 4 sample FeCl3.

[0063] Comparative Example 7

[0064] The difference between this comparative example and Example 8 is that this comparative example directly uses the same amount of FeSO4 without going through steps 1, 2, and 3, to obtain the comparative example 5 sample FeSO4.

[0065] The present invention evaluated the iron loading amount, iron solubility in the gastrointestinal tract, and iron supplementation effect on iron-deficient mice for the above examples and comparative examples, as follows:

[0066] 1. Test of iron loading

[0067] The gels from different examples / comparative examples were soaked in distilled water, then frozen at -80°C for 24 hours and then freeze-dried in a vacuum freeze dryer. The gels were removed, crushed, passed through an 80-mesh sieve, and dissolved in 10 ml of 0.1 mol / L HCl solution. The mixture was stirred at 100 rpm and uniformly dissolved. A 5 ml sample was filtered through a 0.45 μm microporous membrane as the test solution. The iron loading in the iron (III)-oxidized starch gel was determined by o-phenanthroline UV spectrophotometry.

[0068] 2. Test of Iron Dissolution in the Gastrointestinal Tract

[0069] The paddle method specified in the 2010 edition of the Pharmacopoeia of the People's Republic of China was used for determination, and some adjustments were made thereon. The gel powders of different embodiments / comparative examples were placed in 100 mL of dissolution medium and simulated under the conditions of a water bath temperature of 37°C and a stirring speed of 100 r / min. According to the transportation process of food in the stomach and small intestine, the entire in vitro simulation experiment was divided into two processes: 2 hours in the stomach and 3 hours in the small intestine. After the gastric juice simulation process was completed, the dissolution solution was quickly replaced. The sampling time intervals were set to: 60 min, 120 min, and 150 min. 2 mL of dissolution solution was taken each time and filtered through a 0.45 μm microporous filter membrane. The iron content in the dissolution solution was determined by o-phenanthroline ultraviolet spectrophotometry.

[0070] 3. In vitro simulated digestion test

[0071] 1.00 g of different oxidized starch gel materials (calculated on a dry basis) were dissolved in 20 mL of acetic acid-sodium acetate buffer and preheated at 37°C. In the simulated oral cavity phase, salivary α-amylase was first added to a final enzyme activity of 7.5 U / mL, and the pH of the mixture was adjusted to 7.0 to simulate the oral environment. Subsequently, the mixture was shaken at 140 rpm in a 37°C constant-temperature shaker for 2 minutes. In the simulated gastric fluid phase, the system pH was adjusted to 1.2, pepsin was added, and the mixture was shaken continuously at 140 rpm in a 37°C constant-temperature water bath shaker for 2 hours to simulate the digestion of the oxidized starch gel in the stomach. In the simulated small intestine phase, the system pH was adjusted to 6.8, 5 mL of the mixed enzyme solution was added, and the mixture was shaken continuously at 140 rpm in a 37°C constant-temperature water bath shaker for 3 hours to simulate the digestion of the oxidized starch gel in the small intestine. After 2 minutes of simulated oral digestion, 120 minutes of gastric digestion, and 140, 180, 240, and 300 minutes of small intestinal digestion, 0.5 mL of digestive fluid was removed and placed in 20 mL of 70% ethanol to inactivate the enzyme. Finally, the ethanol solution was centrifuged at 4000 rpm for 5 minutes, and the supernatant was collected for later use and absorbance was measured using a GOPOD kit.

[0072] 4. Establishment of an Iron Deficiency Anemia Mouse Model and Evaluation of the Effect of Iron Supplementation

[0073] The test mice were raised in an SPF-grade animal house with a sanitary environment. Before the formal experiment began, the experimental mice underwent a week of adaptive feeding, during which they were free to consume basic feed. One week later, 8 of them were fed basic feed (blank control group), and the other mice were fed low-iron feed for 28 days. In addition to feeding low-iron feed, they were also required to bleed from the tail vein twice a week, 0.1 mL each time, for a total of 8 times. At the same time, in order to prevent the mice from gnawing on the cages, stainless steel cages were used to avoid iron contamination. During the feeding period, tail vein blood was collected from each group of mice every week, and body weight and blood routine indicators were measured. When HB dropped below 90 g / L, the model was successful. At the same time, the daily food and water intake of the test mice were recorded in detail, and their mental state, vitality, etc. were observed.

[0074] After the 28-day intervention, the successfully modeled mice were randomly divided into groups based on their body weight and hemoglobin levels. The drug was administered daily by gavage for four consecutive weeks. The Example and Comparative Example groups received 0.2 mL of the drug by gavage, while the model and blank control groups received the same volume of normal saline. All groups had free access to water and food during this period.

[0075] Subsequently, we systematically explored the effects of different experimental groups and control groups on physiological and biochemical metabolic indicators related to iron deficiency anemia, such as body weight, routine blood indicators, and serum iron deficiency indicators of mice with iron deficiency anemia, and studied their effects on intervening in iron deficiency anemia.

[0076] Result analysis:

[0077] Since iron ions cannot exist in a free form under non-acidic conditions, and the carboxyl groups of oxidized starch will be protonated under acidic conditions, the pH value of the gel can be adjusted in sections by using the 4D printing processing method, thereby enhancing the complexing ability of the carboxyl groups with iron ions. First, the effect of immersion in different pH alkaline solutions on the 4D printed iron-starch gel was studied. Figure 1 It can be seen that after the sample is soaked in alkaline solution with pH = 12 for 10 minutes, part of the structure of the gel is dissociated; after the sample is soaked in alkaline solution with pH = 8 and pH = 10 for 10 minutes, the overall structure of the gel is not destroyed and remains original.

[0078] The cross-sectional structures of the gels of different embodiments are as follows: Figure 2 As shown in the figure, the sample presents a lamellar three-dimensional network structure, which is similar to Fe 3+ A complexation reaction occurs, forming a new cross-linked structure inside the gel, with uniform and dense network pores, and the network structure of 4D-FeOMS10% is more uniform and stable. Figure 2 As shown in the EDC image, Fe 3+Significant characteristic peaks are shown on the horizontal axes of 0.6keV, 6.4keV and 7.0keV, indicating that Fe 3+ There are three binding states in iron-starch gel. The first is to form a stable ionic bond with the deprotonated carboxyl group through electrostatic interaction. The second is to react with the active hydroxyl groups on the oxidized starch molecular chain to form a weaker coordination bond. The third is to exist in the gel network pores in a free state.

[0079] Figure 3 From the scanning electron microscope images of different embodiments and comparative examples, it can be seen that with the addition of iron ions, the network pore size distribution of the embodiment samples becomes sparse, indicating that with the addition of iron ions, a large number of hydrogen ions exist in the system, destroying the original hydrogen bond interaction of starch, resulting in fewer cross-linking points formed between starch molecular chains, and with the increase of the amount of iron ions added, the cross-linking points between the starch molecular chains become less and less. Under the same iron addition amount, the network structure of the embodiment samples is denser than that of the comparative example samples. This is because the carboxyl groups of the oxidized starch are deprotonated after alkali solution immersion, and part of the Fe 3+ Complexation with hydroxyl groups to form new coordination bonds, and part of Fe 3+ The new ionic bonds formed with the carboxyl groups increased the cross-linking points in the network structure, making the mesh structure of the gel network smaller and the density enhanced. When the iron addition amount was greater than 10%, the difference in network density between 4D-FeOMS-15% and 3D-FeOMS-15% was reduced, which may be due to the Fe 3+ The coordination and ionic bond cross-linking effects are close to saturation compared to 4D-FeOMS-10%, so the density change of its network structure after 4D printing stimulation is not as obvious as the density change of FeOMS-10% gel network structure.

[0080] It can be seen from Table 1 that as the amount of iron added increases, the iron loading of the examples increases.

[0081] The growth of the loading of 4D-FeOMS-15% sample is significantly lower than that of the first two samples, which may be due to the Fe 3+ The resulting complexation is saturated, and excess iron ions exist in the gel in a free form. They are lost to the soaking liquid during the soaking process, resulting in a decrease in iron loading. At the same iron addition level, the iron loadings of different examples, 4D-10% FeOMS1, 4D-Fe2OMS-10%, 4D-FeOMS2-10%, and 4D-FeOPS-10%, are similar, indicating that different oxidation methods, different iron valence states, and different starch varieties have no significant effect on iron loading, demonstrating the applicability of this patent.

[0082] In addition, under the same iron addition amount, the iron loading of 3D printed iron-oxidized starch gel 3D-FeOMS-10% and unoxidized 4D-FeMS is lower than that of 4D printed iron-oxidized starch gel 4D-FeOMS-10%. This is because the alkali solution soaking changes the pH of the gel system, deprotonates the carboxyl groups of the oxidized starch, and reacts with the Fe in the system. 3+ Forming a more stable complex bond, while shrinking the entire starch gel network, slowing down the Fe 3+ Lost into the soaking solution, thereby increasing the iron loading.

[0083] Table 1 Iron loading of different samples

[0084]

[0085] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0086] As shown in Table 2, the digestion rates of the different Examples / Comparative Examples in the mouth and stomach (first 120 minutes) were extremely low, with a digestibility of less than 2%. However, the digestibility increased rapidly in the proximal small intestine (120 minutes to 140 minutes), and was greater than 50%. This indicates that the iron-starch gels of the Examples are enzymatically digested by amylase in the proximal small intestine, which facilitates the subsequent absorption of iron ions and their polysaccharide-iron complexes by the villi epithelial cells of the small intestine.

[0087] Table 2 Digestibility of different embodiments / comparative examples

[0088]

[0089]

[0090] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0091] Comparing the iron dissolution rates of different embodiments and comparative examples, the samples were dissolved in artificial simulated gastric fluid in the first 120 min. From Table 3, it can be seen that the iron dissolution rate of the embodiment at 60 min was much lower than that of the comparative example, both of which were less than 30%, indicating that the alkaline pH stimulation of 4D printing caused the iron to dissolve in the sample. 3+It complexes with the carboxyl groups of oxidized starch to form a stable oxidized starch-iron complex. After 120 minutes, the sample is in artificial intestinal fluid. During this period, due to the addition of pancreatic amylase, the oxidized starch is hydrolyzed into oligosaccharides and glucose in large quantities. Therefore, the solubility of the iron element in each embodiment increases rapidly from 120 to 150 minutes. As the amount of iron added increases, the solubility of the embodiment increases. Under the same iron addition amount, the iron loading of different embodiments 4D-10% FeOMS1, 4D-Fe2OMS-10%, 4D-FeOMS2-10% and 4D-FeOPS-10% is close, indicating that different oxidation methods, different iron valence states and different varieties of starch have no significant effect on iron solubility, indicating the applicability of this patent.

[0092] Table 3 Iron dissolution rates of different embodiments / comparative examples

[0093]

[0094] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0095] The various blood indicators and weight changes of mice during the modeling process are shown in Tables 4 and 5. Before modeling, the blood indicators of mice in the normal feed group and the iron-deficient feed group were all within the normal range. However, four weeks after modeling, the HGB of the low-iron feed group was significantly lower than before modeling. This is because the low-iron feed group lacked sufficient iron intake, resulting in insufficient iron storage in the body, which affected the synthesis of hemoglobin. Iron is an important component of hemoglobin, and iron deficiency can lead to anemia. As the intervention time of the low-iron feed group prolonged, the mice showed obvious hair loss on the back, weight loss, obvious paleness in the limbs and ears, slow movement, and yellowish stool. The normal feed group did not show the above phenomena, and after four weeks of intervention, the weight of mice in the low-iron feed group was lighter than that of mice in the normal feed group. By comparing physiological indicators and blood routine indicators, it can be considered that the iron deficiency anemia mouse model was successfully established.

[0096] Table 4 Blood parameters of mice before and after modeling

[0097]

[0098] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0099] Table 5 Changes in body weight of mice before and after modeling

[0100]

[0101] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0102] Table 6 shows the weight changes of mice in each group after 28 days of intervention. Compared with the blank group, the weight of mice in the model group and OMS group is about 6g lower, indicating that iron deficiency anemia can affect the physical development of mice and slow their weight gain. The weight of mice in each group of the embodiment recovered rapidly during the intervention period, and there was no significant difference in weight between them and the blank group mice after 28 days. Although the weight of mice in the control group was significantly higher than that of the model group, it still did not return to normal levels. The blood iron saturation of mice in each group after 28 days of intervention can be calculated by serum iron content and total iron binding capacity, as shown in Table 7. Blood iron saturation is the ratio of iron bound to transferrin in the blood, which reflects the utilization of iron in the blood and the degree of iron storage. From the blood iron saturation data of mice in the model group, it can be seen that when the body is in an iron-deficient state, serum iron content decreases and total iron binding capacity increases, resulting in a decrease in blood iron saturation. Although the blood iron saturation of mice in each control group has been improved to a certain extent, it is still significantly different from the blank group. The blood iron saturation of mice in each example group was higher than that of normal mice in the blank group, indicating that the 4D printed iron-oxidized starch gel intervention significantly improved the body's iron deficiency. The above results show that each example group can effectively treat the anemia symptoms of mice.

[0103] Table 6 Body weight changes of mice in each group after 28 days of intervention

[0104]

[0105] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter marking indicates significant differences (p < 0.05).

[0106] Table 7 Changes in serum iron indexes of mice in each group after 28 days of intervention

[0107]

[0108] Note: The distribution of variables in the table is described as "mean ± standard deviation", and letter markings indicate significant differences (p<0.05).

[0109] The above is a further detailed description of the present invention in conjunction with specific preferred embodiments, and the specific implementation of the present invention should not be considered to be limited to these descriptions. Those skilled in the art will recognize that several equivalent substitutions or obvious variations can be made without departing from the scope of the present invention, and that any equivalent performance or application should be considered to fall within the scope of protection of the present invention.

Claims

1. A method for preparing a starch gel material based on 4D printing technology, characterized in that, The following steps are involved: (1) gelatinizing a mixture of carboxyl-containing starch and water, and adding a salt containing a divalent or higher metal cation to obtain a uniform mixture; (2) transferring the mixed material into the barrel of a 3D printer, forming the mixed material by hot extrusion 3D printing, obtaining a 3D printed sample, and performing 4D printing stimulation; the 4D printing stimulation is alkaline solution stimulation, and the pH of the alkaline solution is 8-12; (3) Immediately freeze the 4D printed sample and then freeze-dry it in a vacuum to obtain a starch gel material; The divalent or higher metal cations in step (1) are one or more of ferric ions, ferrous ions, calcium ions and zinc ions; the concentration of the carboxyl-containing starch is 10-50%, and the salt containing the divalent or higher metal cations accounts for 1%-50% of the dry basis of the carboxyl-containing starch.

2. The preparation method according to claim 1, characterized in that The carboxyl-containing starch is one or more of oxidized starch and carboxymethyl starch.

3. The preparation method according to claim 2, characterized in that The starch is one or more of corn starch, cassava starch, potato starch, chestnut starch and modified starches thereof.

4. The preparation method according to claim 2, characterized in that The preparation method of oxidized starch comprises the following steps: mixing starch with a buffer solution, then adding an oxidant, stirring and reacting, the reaction temperature is 0-40°C, the reaction time is 4-24 hours, and after the reaction is completed, washing and drying to obtain the oxidized starch.

5. The preparation method according to claim 4, characterized in that The oxidant is sodium hypochlorite, TEMPO or laccase; the buffer is phosphate buffer; and the mass concentration of starch in the buffer is 0.01-0.5 g / mL.

6. The preparation method according to any one of claims 1 to 5, characterized in that The gelatinization conditions in step (1) are 60-110° C. for 3-60 minutes.

7. The preparation method according to any one of claims 1 to 5, characterized in that The conditions for the hot extrusion 3D printing molding are: a holding temperature of 55 to 100° C., a holding time of 5 to 30 minutes, and a cube, cuboid, or cylindrical model.

8. The preparation method according to any one of claims 1 to 5, characterized in that The pH of the alkali solution is 8-10, and the alkali solution stimulation time is 0.1h-24h; the alkali solution is one or more of sodium hydroxide, potassium hydroxide, carbonate, bicarbonate, sulfite, acetate, silicate, phosphate, metaaluminate, hypochlorite and buffer solution thereof.

9. the starch gel material obtained by the preparation method described in any one of claim 1-8.

10. The use of the starch gel according to claim 9, characterized in that The starch gel material is used as a starch-based mineral supplement and a delivery system material.

Citation Information

Patent Citations

  • 4D printing method of hericium erinaceus gel food

    CN111248473A

  • Starch gel hemostatic material based on 3D printing technology and preparation method and application thereof

    CN114191601A